Mood states and sports results of a team throughout the second phase of the national futsal league Estados de humor e resultado esportivo de uma equipe ao longo da segunda fase da liga nacional de futsal - Bevilacqua G.G.* (2019)
© Universidade de Brasilia.This study evaluated the moods states of professional futsal players during the second phase of the Brazilian Futsal League 2012. The sample was composed of 15 male athletes and the instrument used for evaluation was the Brunel Mood Scale. The results show that there were significant differences (p<0.05) in mood states on the previous day, pregame and post-game. The team presented mood states corresponding to the iceberg profile in almost all times: constant and high vigor, except for the post-game defeats, and fatigue with low levels, which were elevated in the post-game. It was concluded that mood states can positively or negatively interfere with team sports performance.